"Long ball" and "balls deep": a critical reading of female coach-learners' experiences of the UEFA A licence. Issue 1 (2nd January 2021) - Sawiuk, Rebecca; Lewis, Colin J.; Taylor, William George
ABSTRACT: In this article we present a critical reading of female coach-learners' experiences of the Union of European Football Association's Advanced Licence (UEFA A), which at the time of writing have been largely ignored. It comes at a point when The Football Association's policy, the 2017–2020 Gameplan for Growth Strategy, which focuses on the women's game, has been completed. We wanted to understand better the challenges faced by female coaches as they navigate their way through the male-dominated educational programmes. We interviewed nine female UEFA A Licence holders who had participated in differing cohorts across a ten-year span. Interpreting the female coach-learners' experiences through a critical and broadly poststructuralist lens reveals how the language, structure and assumptions inherent in the course impact female coach-learner experiences. The data exposes a catalogue of androcentric assumptions, toxic masculinity, sexualised language, dismissive practices and an ignorance of the women's game.